Prevalence, Association and Differences Between Ultra-Processed Food Consumption and Emotional Eating Among Male Varsity Badminton Players and Non-Athlete University Students - Haq, Maghfoor ul; Ali, Asif; Ahmed, Fariq; Azam, Muhammad; Ahmad, Haris (Pakistan Journal of Humanities and Social Sciences, 2024)
This research was aimed at exploring the prevalence, association and differences between Ultra-Processed Food (UPF) consumption and emotional eating among male varsity badminton athletes and non-athlete university students. To conduct this study, a sample of 112 male students was drawn from eight universities from a major city in Pakistan. The sample included 56 varsity badminton athletes (M = 21.34, SD = 1.81) and 56 non-athlete students (M = 21.79, SD = 1.42). The tool to gather data involved a demographic questionnaire along with Highly Processed Food Consumption Questionnaire and the Emotional Eating Questionnaire. The SPSS version 27 was applied for analysis and investigation of data (IBM Corp, 2020). Results showed that male varsity badminton players reported low prevalence of both UPF consumption and emotional eating as compared to non-athlete university students. Additionally, it was also observed that there was a significant positive association between UPF consumption and emotional eating among both groups. Lastly, male varsity badminton players reported low UPF consumption as compared to non-athlete university students. However, no significant mean differences in emotional eating scores were reported among both groups. These findings highlight the significance of participating in individual sports particularly badminton to counter emotional eating and reduce the consumption of UPFs among varsity students.